Filmwissenschaftliche Genreanalyse eine Einführung - Kuhn, Markus 1972-; Haffke, Irina 1976-; Weber, Nicola Valeska (De Gruyter, 2013)
Genre theory is among the fundamental approaches to the historical and systematic understanding of motion pictures. This introductory volume provides an overview of the use of genre analysis in film studies and about the main motion-picture genres. For each of the genres presented, the book includes an exemplary film analysis. It also offers an interdisciplinary view on the utility of the concept of genre in other media
Keywords: Lehrbuch; Filmanalyse; Theorie; Filmgenre; Film genres; Electronic books